2017
DOI: 10.1111/hsc.12526
|View full text |Cite
|
Sign up to set email alerts
|

Identifying acceptable components for home-based health promotion services for older people with mild frailty: A qualitative study

Abstract: Mild frailty is common in later life, increasing the risk of hospitalisation, loss of independence and premature death. Targeted health promotion services may reduce adverse outcomes and increase quality of life; however, effective, well-developed theory-based interventions are lacking. We aimed to explore perceptions of health promotion behaviours undertaken by older people with mild frailty, barriers and facilitators to engagement, and identify potential components for new home-based health promotion service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…23,24,38 Models of home support should, therefore, reflect this complexity, and address cognitive and physical dependency as highlighted in this study, including a broader range of personalised supports for social isolation, mental health, cultural, and personal aspects. 37,[39][40][41][42] This approach has been recommended by the WHO. 2 A strength of this study is the large sample size.…”
Section: Discussionmentioning
confidence: 99%
“…23,24,38 Models of home support should, therefore, reflect this complexity, and address cognitive and physical dependency as highlighted in this study, including a broader range of personalised supports for social isolation, mental health, cultural, and personal aspects. 37,[39][40][41][42] This approach has been recommended by the WHO. 2 A strength of this study is the large sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In our development work, qualitative interviews with older people, carers and health professionals revealed that a health promotion service should cover a broad range of domains, and use mechanisms such as providing information and signposting, emotional and practical support, and boosting motivation (Frost et al, ; ). Although the COM‐B model (Michie et al, ), which underpinned the design of HomeHealth, has been increasingly used for behaviour change health promotion across different disciplines, few studies explore older people's experiences with this approach, and it is the first to focus on people who are mildly frail.…”
Section: Discussionmentioning
confidence: 99%
“…66 Although various types of frailty intervention models have been developed and investigated, there is a considerable degree of heterogeneity in terms of optimal intervention type, sample size, population characteristic, setting, baseline frailty status, frailty definition, and outcomes, and most findings are inconclusive. [67][68][69][70][71][72][73][74] At present, it is therefore not possible to conclude what intervention is the most effective and appropriate. Overall, multi-domain intervention trials, which have been frequently conducted, 75,76 and many of which included an exercise component, seemed to have some favorable effects (although not in all trials) compared with mono-domain interventions or the control.…”
Section: Interventions For Frailtymentioning
confidence: 99%